Bortezomib and etoposide combinations exert synergistic effects on the human prostate cancer cell line PC-3 - ARAS, BEKIR (Oncol Lett, 2016)
Novel treatment modalities are urgently required for androgen-independent prostate cancer. In order to develop an alternative treatment for prostate cancer, the cytotoxic effects of the 26S proteasome inhibitor bortezomib, either alone or in combination with the two commonly used chemotherapeutic agents irinotecan and etoposide, on the human prostate cancer cell line PC-3 were evaluated in the present study. The PC-3 cell line was maintained in Dulbecco's modified Eagle's medium with 10% fetal bovine serum and treated with various doses of bortezomib, irinotecan, etoposide or their combinations. The growth inhibitory and cytotoxic effects were determined by water-soluble tetrazolium (WST)-1 assay, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay or iCELLigence system. The combination index values were determined by the Chou-Talalay method. The half maximal inhibitory concentration (IC50) value of bortezomib on the PC-3 cell line was determined to be 53.4 nM by WST-1 assay, whereas the IC50 values of irinotecan and etoposide were determined to be 2.1 and 26.5 µM, respectively. These results suggest that the 26S proteasome inhibitor bortezomib is more potent, compared with irinotecan and etoposide, in the androgen-insensitive and tumor protein p53-null cell line PC-3. The combined effects of bortezomib+irinotecan and bortezomib+etoposide were also tested on PC-3 cells. The effect of bortezomib+irinotecan combination was not significantly different than that produced by either monotherapy, according to the results of iCELLigence system and MTT assay. However, 40 nM bortezomib+5 µM etoposide or 40 nM bortezomib+20 µM etoposide combinations were observed to be more effective than each drug tested alone. The results of the current study suggest that bortezomib and etoposide combination may be additionally evaluated in clinical trials for the treatment of hormone-refractory prostate cancer.